Effect of Acid and Alkaline Environment on Dynamic Strength and Porosity Characteristics of Bursting Liability Coal. (17th August 2021) - Li, Lei; Fan, Jiangbo; Liu, Ningning; Gong, Shuang; Yang, Daming
Abstract : In order to investigate the influence of acid and alkaline environment on dynamic strength and porosity characteristics of bursting liability coal, scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis were used to compare the microstructures of coal with different bursting liabilities. A split Hopkinson bar (SHPB) was used to test the dynamic compressive strength and tensile strength of coal samples with different bursting liabilities. The results show that the surface micromorphology and structure characteristics of coal samples with different bursting liabilities are representatives, which can be used as an auxiliary basis to determine the bursting liability of coal seam. The microstructure of coal with strong bursting liability is characterized by mylonitic, fragmentary, and brecciated structure, and the microstructure is diverse and complex. However, the microstructure of no bursting liability coal is single and uniform. Coal with strong bursting liability shows tensile, compressive, and shear cracks produced by tectonic action, and the distribution of cracks is complicated. The development of fissures is greatly affected by the degree of coal metamorphism, organic components, minerals, and other factors. Under acidic and alkaline environments, the decrease amplitude of tensile strength of coal is obviously larger than that in neutral solution, which indicates that under the action of acid-based solution soaking, the easily soluble minerals in coal react with hydrogen ions and hydroxyl ions in solution obviously. Porosity increment in acidic environment is much larger than that in alkaline and neutral environments. The strong bursting liability coal is more sensitive to acidic environment, while the no bursting liability coal is more sensitive to alkaline environment.